The Logic of the Rhythm: Notes for a Classification of the Readings of Piedra de sol by Octavio Paz - López Soto, Luis Alberto (2023)
Piedra de sol (1957) by Mexican poet Octavio Paz is a long poem. From its publication to the present, it has been the subject of various readings. In this article an analysis of the poem is made and, above all, a description, analysis and classification of the readings provided by specialized critics with the aim of drawing a guideline that explains the logic and evolution of such interpretations. The theoretical concepts of immanence and transcendence are used to expose chronologically those readings that observe in Paz's text a poetic manifesto of a verbal structure or an extratextual discourse (philosophical, religious, anthropological, etc.), or the fusion of these two readings. All this to propose that the notion of rhythm (found in the last readings of the poem) is an analytical and interpretive key that unites the immanent and the transcendent, and represents, therefore, a high point of criticism.